INCOME AND FEASIBILITY ANALYSIS OF THE TOFU MANUFACTURING INDUSTRY (CASE STUDY ON PINK JAYA HOME INDUSTRY IN OEBUFU SUB-DISTRICT, OEBOBO DISTRICT, KUPANG CITY) - Hina, Samuel; Bano, Maria; Chamdra, Santhy (Buletin Ilmiah Impas, 2025)
The objectives of this study are: (1) To determine the level of income and business feasibility of tofu production at the Pink Jaya Home Industry in Oebufu Sub-district, Oebobo District, Kupang City. This research uses a case study method. It was conducted in Oebufu Sub-district, Oebobo District, Kupang City. The sampling method used was the saturated sampling technique. Data analysis methods included income analysis and R/C ratio and B/C ratio analysis. The results of the study are as follows: (1) The income from tofu production at the Pink Jaya Home Industry in Kupang City from January to May 2024 amounted to IDR 185,890,885, with an average monthly income of IDR 37,178,177. (2) The R/C ratio value for the tofu business at the Pink Jaya Home Industry in Kupang City from January to May 2024 was 1.27, indicating that since the R/C ratio is greater than 1, the business is considered feasible and profitable to operate.